Phytochemical Analysis, Antimicrobial and Antioxidant Properties of Thymus zygis L. and Thymus willdenowii Boiss. Essential Oils - Fatima zahrae Radi; Mohamed Bouhrim; Hamza Mechchate; Mohammed Al-zahrani; Ashraf Ahmed Qurtam; Abdulmalik M. Aleissa; Aziz Drioiche; Nadia Handaq; Touriya Zair (Plants, 2021)
Essential oils (EOs) are chemical products produced by odoriferous glands from a variety of plants. These essential oils have many health benefits: antiseptic, anti-inflammatory and antimicrobial activities. So due to these medicinal properties, the present study was designed to analyze essential oils of Thymus zygis L. and Thymus willdenowii Boiss. for their chemical composition and biological activities. These two thyme species were collected from the region of Ifrane, Middle Atlas of Morocco. The EO was obtained by hydrodistillation, and the yields were 5.25% for T. zygis and 3.00% for T. willdenowii. The chemical composition of the EOs was analyzed by gas chromatography coupled with mass spectrometry (GC-MS), and the results showed that T. zygis EO is dominated by carvacrol (52.5%), o-cymene (23.14%), and thymol (9.68%), while the EO of T. willdenowii contains germacrene D (16.51%), carvacrol (16.19%), and geranyl acetate (8.35%) as major compounds. The antioxidant activity assessed by Diphenylpicrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays revealed that both EOs have excellent antioxidant activities; by DPPH it resulted in IC50 = 6.13 ± 0.11 for T. zygis and 6.78 ± 0.3 µg/mL for T. willdenowii, while the one by FRAP yielded EC50 = 2.46 ± 0.01 (T. zygis) and 5.17 ± 0.2 (T. willdenowii) µg/mL. The antimicrobial activity of the two essential oils was evaluated against six bacterial strains and five fungal strains by the disk diffusion method to determine the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC). The EOs revealed variable antimicrobial activities against the different tested microbial strains and showed strong antimicrobial activities, even against strains known as multi-resistant to antibiotics (Acinetobacter baumannii) at low concentrations (2 µL/mL). T. zygis EO showed the most powerful activity against all the studied bacteria, while that of T. willdenowii recorded moderate activity when tested against Shigella dysenteriae and Salmonella Typhi. With inhibition diameters that vary between 75 mm and 84 mm for concentrations of 2 µL/mL up to 12 µL/mL, S. aureus was shown to be the most sensitive to T. zygis EO. For the antifungal activity test, T. zygis EO showed the best inhibition diameters compared to T. willdenowii EO. These results showed that T. zygis EO has more powerful antioxidant and antimicrobial activities than T. willdenowii EO, therefore, we deduce that thyme EOs are excellent antioxidants, they have strong antimicrobial properties, and may in the future represent new sources of natural antiseptics that can be used in pharmaceutical and food industry.